Lifestyle Methods for Prevention of Alzheimer's Disease From the Perspective of Traditional Persian Medicine. (July 2016) - Tajadini, Haleh; Choopani, Rasool; Saifadini, Rostam
Alzheimer's disease is considered as a major problem for society health since it affects interpersonal and social relationships. With regard to the global attention toward complementary medicine, search for preventive, diagnostic, and treatment strategies in complementary medicine schools such as the old dynamic doctrine of traditional Persian medicine seems to be necessary. In this type of medicine, description and analysis of the disease and preventive and treatment methods have great importance. The present study provides a useful classification of recommendations for prevention and control of Alzheimer's disease. Prevention is prior to the treatment and is easier and less costly. Recommendations mentioned in traditional Persian medicine texts for prevention of Alzheimer's disease provide fields of clinical and complementary studies for researches.